2012
DOI: 10.1017/s003329171200178x
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception but not peer reputation of bullying victimization is associated with non-clinical psychotic experiences in adolescents

Abstract: Background. Bullying victimization may be linked to psychosis but only self-report measures of victimization have been used so far. This study aimed (a) to investigate the differential associations of peer-nominated versus selfreported victim status with non-clinical psychotic experiences in a sample of young adolescents, and (b) to examine whether different types of self-reported victimization predict non-clinical psychotic experiences in these adolescents.Method. A combination of standard self-report and pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 37 publications
5
33
0
Order By: Relevance
“…The epidemiological design of the present study does not allow for the assessment of feelings of ‘defeat’ in the context of an actual social setting. A recent study has attempted to disentangle the differences between the personal interpretation of social situations on the one hand, and actual social interactions as experienced by others, by comparing self‐reports and peer reports of peer victimization . In this study, it was found that not peer reports, but the subjective (personal) reports of victimization were associated with presence of psychotic experiences.…”
Section: Discussionmentioning
confidence: 86%
“…The epidemiological design of the present study does not allow for the assessment of feelings of ‘defeat’ in the context of an actual social setting. A recent study has attempted to disentangle the differences between the personal interpretation of social situations on the one hand, and actual social interactions as experienced by others, by comparing self‐reports and peer reports of peer victimization . In this study, it was found that not peer reports, but the subjective (personal) reports of victimization were associated with presence of psychotic experiences.…”
Section: Discussionmentioning
confidence: 86%
“…The data on bullying, for example, may be inaccurate, and we had no collateral accounts. Its definition is in part subjective, and there may be over-or underreporting (33) . People without psychotic symptoms may omit stressful events, and those who suffer from them may engage in an "effort after meaning", and thus be more inclined to remember them.…”
Section: The Follow-up Analysismentioning
confidence: 99%
“…Thus, peer nominations rather than self-reports were used to measure behavior during bullying episodes. Several studies (Bouman et al, 2012;Gromann, Goossens, Olthof, Pronk, & Krabbendam, 2013;Olthof et al, 2011;Pronk, Olthof, & Goossens, 2014;Reijntjes, Vermande, Goossens, et al, 2013;Reijntjes, Vermande, Olthof, et al, 2013) indicated that peer-nominated bullying behavior is associated in theoretically meaningful ways with various variables, including peer-nominated popularity and resource control, teacher-rated resource control, peer-rated likeability, and self-perceived social competence. However, the proportions of peer-reported bullying behavior should not be interpreted as the degree of behaving in that role; the values actually represent the degree of others' awareness of the behavior.…”
Section: Limitationsmentioning
confidence: 99%